Structural analysis of historical constructions: anamnesis, : anamnesis, diagnosis, therapy, controls : proceedings of the 10th international conference on structural analysis of historical constructions (SAHC, Leuven, Belgium, 13-15 September 2016) /: anamnesis, diagnosis, therapy, controls : proceedings of the 10th international conference on structural analysis of historical constructions (SAHC, Leuven, Belgium, 13-15 September 2016). (2016) - Unknown
No abstract available